2019
DOI: 10.1155/2019/7106951
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy of Virtual Reality Rehabilitation after Spinal Cord Injury: A Systematic Review

Abstract: Background Spinal cord injury (SCI) is often associated with long-term impairments related to functional limitations in the sensorimotor system. The use of virtual reality (VR) technology may lead to increased motivation and engagement, besides allowing a wide range of possible tasks/exercises to be implemented in rehabilitation programs. The present review aims to investigate the possible benefits and efficacy of VR-based rehabilitation in individuals with SCI. Methods An electronically systematic search was … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
46
2
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 79 publications
(65 citation statements)
references
References 63 publications
4
46
2
2
Order By: Relevance
“…The present findings are supported by the structured review carried out by Yeo et al [ 28 ], which analyzed the effectiveness of VR therapy for improvement of mobility and showed potential benefits on balance. Furthermore, our results match with those obtained by de Araújo et al [ 29 ] and Abou et al [ 30 ], who suggested that VR-based rehabilitation may lead to positive effects on balance in patients with SCI. Conversely, the present findings do not match with those obtained by our previous meta-analysis [ 3 ], performed to assess the effects of VR interventions on functional performance in patients with SCI.…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…The present findings are supported by the structured review carried out by Yeo et al [ 28 ], which analyzed the effectiveness of VR therapy for improvement of mobility and showed potential benefits on balance. Furthermore, our results match with those obtained by de Araújo et al [ 29 ] and Abou et al [ 30 ], who suggested that VR-based rehabilitation may lead to positive effects on balance in patients with SCI. Conversely, the present findings do not match with those obtained by our previous meta-analysis [ 3 ], performed to assess the effects of VR interventions on functional performance in patients with SCI.…”
Section: Discussionsupporting
confidence: 92%
“…They included seven case series and two randomized controlled trials and concluded that VR is effective to improve balance and posture. A systematic review conducted by Araújo et al [ 29 ], aiming to evaluate the benefits of VR in patients with SCI, included 25 studies; 12 of them used a pre-post design without a control group, 13 were controlled in a parallel or crossover design, and only 11 studies used randomization between groups. They suggested that VR interventions could provide benefits on balance and motor function recovery.…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, the statistical analysis showed favorable results of CPT on the functional independence measured by the FIM scale. Our results match with the findings of de Araújo et al [ 27 ], who reported no solid conclusions about the efficacy of VR interventions on quality of life. The authors reported that this can be attributed to the lack of methodological quality and statistical power observed.…”
Section: Discussionsupporting
confidence: 91%
“…Different recent reviews analyzed the potential use of VR-based neurorehabilitation in patients with SCI. The systematic review conducted by de Araújo et al [ 27 ] concluded that VR therapy could be effective in improving aerobic function, balance, pain level and motor function, but the review was not restricted specifically to assess the quality of life through controlled trials. Villiger et al [ 28 ] suggested that VR interventions may be useful as a neurorehabilitation tool to improve motor function in subjects with a chronic SCI, but authors only analyzed the effects provided by home-based VR interventions.…”
Section: Introductionmentioning
confidence: 99%
“…This hypothesis is supported by a recent study which highlighted the beneficial effects of VR therapy on psychological and motivational aspects of individuals with SCI. 37 By increasing the motivation and providing a safe environment, VR therapy may enhance the interest of individuals with SCI to exercise. Improving interest, participation levels, and confidence might lead to adherence to the therapy 10 and improvement in standing balance in this population.…”
Section: Discussionmentioning
confidence: 99%